2017
DOI: 10.3324/haematol.2017.174177
|View full text |Cite
|
Sign up to set email alerts
|

A distinct subtype of Epstein-Barr virus-positive T/NK-cell lymphoproliferative disorder: adult patients with chronic active Epstein-Barr virus infection-like features

Abstract: The characteristics of adult patients with chronic active Epstein-Barr virus infection are poorly recognized, hindering early diagnosis and an improved prognosis. We studied 54 patients with adult-onset chronic active Epstein-Barr virus infection diagnosed between 2005 and 2015. Adult onset was defined as an estimated age of onset of 15 years or older. To characterize the clinical features of these adults, we compared them to those of 75 pediatric cases (estimated age of onset <15 years). We compared the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…Some patients rapidly develop severe complications, such as multi-organ dysfunction and malignant lymphomas, whereas others remain stable without therapeutic intervention (12). Initially, CAEBV was thought to mainly be a disease of childhood, but, recently, increasing numbers of adult cases have been identified with slightly different clinical features compared to those of pediatric cases (13, 14).…”
Section: Definitions and Brief Description Of Representative Ebv Disementioning
confidence: 99%
“…Some patients rapidly develop severe complications, such as multi-organ dysfunction and malignant lymphomas, whereas others remain stable without therapeutic intervention (12). Initially, CAEBV was thought to mainly be a disease of childhood, but, recently, increasing numbers of adult cases have been identified with slightly different clinical features compared to those of pediatric cases (13, 14).…”
Section: Definitions and Brief Description Of Representative Ebv Disementioning
confidence: 99%
“…Half of the children (including adolescents) with CAEBV died in 5 years, and most of them died in 10–15 years without radical treatment ( 10 ). Two studies reported that adult-onset CAEBV progresses rapidly, and most of patients died within 5 years ( 22 , 23 ). In our series, 3y-OS was equivalent between adults (≥ 20 years of age at onset) and children (71.4 ± 12.1, 76.6 ± 5.3%, respectively; p = 0.61) ( 6 ).…”
Section: Hsct For Caebv In Various Situationsmentioning
confidence: 99%
“…However, the report mentioned an increase in the number of adult patients. There are some differences between the childhood-onset and adult-onset disease with respect to the clinical features and prognosis [8,9]. Indeed, these may well be different disorders.…”
Section: Epidemiology Of Caebvmentioning
confidence: 99%